Analysis of differential gene expression in potato leaves exposed to low dose ionizing radiation - Yongil Yang; Robert G. Sears; Brianna Jacobs; C. Neal Stewart; Scott C. Lenaghan (Functional & Integrative Genomics, 2026)

Synthetic transcriptional repression systems in plants - Lindsey A. Clark; Alexander C. Pfotenhauer; Scott C. Lenaghan; C. Neal Stewart (Plant Cell Reports, 2026)

Effectiveness of passive trapping and sweep netting for insect pollinator sampling in turf communities - Sara Kirby; Christine C. Fortuin; Nikolay S. Minaev; Casey J. O’Neal; David W. Held; Chih J. Wang; Gerald M. Henry; Jeffrey W. Harris; Isadora Gomes Peres de Souza; JoVonn G. Hill; James D. McCurdy (Journal of Insect Conservation, 2026)
Pollinator communities in urban and peri-urban turfgrass remain poorly characterized despite the ubiquity of lawns and growing interest in management practices that enhance floral resources within these otherwise resource-limited environments. To address this gap, we evaluated the effectiveness of active (sweep netting at multiple times of day) and passive (molasses traps and blue, white, and yellow pan traps) sampling methods for surveying insect pollinators in forb-enhanced bermudagrass plots in Mississippi and Georgia. Eight replicate plots were sampled over the course of one week at two sites, using a randomized complete block design. We identified 4,638 insect pollinator specimens representing 153 distinct taxa. Overall, sweep netting captured more individuals but tended to be biased toward larger, social taxa (e.g., Apis , Bombus ), whereas pan traps collected greater per-sample species richness and disproportionately sampled smaller, solitary taxa. Molasses traps yielded comparatively few individuals and low taxonomic diversity relative to other methods and were therefore excluded from final comparative analyses. Community composition differed significantly among sampling methods. These results demonstrate that no single method adequately captures full pollinator assemblages in forb-enhanced turfgrass systems; a complementary protocol combining sweep netting and pan trapping is recommended for comprehensive pollinator surveys in managed turf landscapes. Implications for Insect Conservation: Although conventional turfgrass monocultures generally provide limited value for insect pollinators, turfgrass-dominated landscapes are widespread in urban and peri-urban environments and therefore represent an opportunity for targeted enhancement through the incorporation of flowering forbs. However, realizing this potential requires unbiased, efficient, and reliable pollinator surveying methods that are specifically tailored to forb-enhanced turf. Here, we provide analyses that quantify the method-specific biases, temporal effects, and complementary strengths of active and passive surveying methods for monitoring pollinator abundance, richness, and community composition.

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

A new chapter of Plant Cell Reports - C. Neal Stewart (Plant Cell Reports, 2026)

The blue carbon potential of coastal driftwood: evidence from the Caribbean coast of Colombia - Nelson Rangel-Buitrago; Mohamed Ben-Haddad; Francois Galgani; William J. Neal; Adriana Gracia C (CATENA, 2025)

The environmental legacy of coastal sandbags - Nelson Rangel-Buitrago; Adriana Gracia C.; Francois Galgani; William J. Neal (Marine Pollution Bulletin, 2025)

Driftwood as a passive retention structure for marine litter - Nelson Rangel-Buitrago; Juan Rangel; Mohamed Ben-Haddad; Francois Galgani; William J. Neal; Adriana Gracia C. (Marine Pollution Bulletin, 2025)

AI cannot be a peer reviewer - C. Neal Stewart; Günther Hahne (Plant Cell Reports, 2025)

Comparison of plant response and phosphorus uptake by ion exchange desorption and chemical extraction for soils under different land uses - Yaqi Zhang; Dingjiang Chen; Lizhong Zhu; Wenxiang Zhou; Shane Campbell; Peng Wang; Neal W. Menzies; Ram C. Dalal (Plant and Soil, 2025)
Aims We quantified the relative significance of phosphorus (P) availability quantity and rate of P desorbed to plant growth using ion exchange membranes on three soils (0–10 cm), initially under native vegetation and converted to either cropping, pasture, or plantation for up to 115 years. Methods Soil P availability parameters were measured by the widely used sodium bicarbonate test (Colwell P), anion exchange membranes and anion + cation exchange membranes either saturated by NaHCO 3 or KCl solution. Plant P parameters measured were dry matter yield, relative yield, and P uptake by Rhodes grass ( Chloris gayana ). Results We found that the quantity of soil P measured by the HCO 3 -anion exchange membrane accounted for up to 90% variability in dry matter yield and P uptake, and the rate of P desorbed by HCO 3 - anion exchange membrane accounted for 81% variability in yield response, while Colwell P was unsuccessful. Conclusion Anion exchange membrane saturated with NaHCO 3 provided superior performance in predicting the availability of soil P to plants compared to the routinely used soil test under different land uses. Thus, wider use of these ion exchange membranes is recommended to provide a more accurate assessment of the amount of plant available P present in soils. This will be beneficial for improving fertiliser P management practices to increase P use efficiency in the face of decreasing P reserves. Moreover, HCO 3 -anion exchange membrane technique will be useful in monitoring excess P applications, and thereby devising practices to reduce environmental P pollution.

Toward a monocot SynBio toolkit: assessing regulatory element performance and eudicot compatibility - David B. May; Alexander C. Pfotenhauer; Bryn L. Concha; Li Li; Samantha M. Jones; Stacee A. Harbison; Lana H. Martin; Lindsey A. Clark; Alessandro Occhialini; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2025)

Comparison of natural abundance and enriched 15N methods to quantify nitrogen fertilizer recovery in maize under field conditions - Sarita Manandhar; Cristina Martinez; Neal W. Menzies; Ram C. Dalal; Michael Bell (Plant and Soil, 2025)

Increased root growth and seed yield in transgenic soybean overexpressing NAC genes GmNAC19 and GmGRAB1 - Mitra Mazarei; Nicole Coffey; Sarah E. A. Shipp; C. Neal Stewart; Tarek Hewezi (Plant Cell Reports, 2025)

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Performance of skimmed milk flocculation and real-time polymerase chain reaction for the concentration, detection, and quantification of Taenia solium in urban wastewater from an endemic region of the Peruvian central highlands - Cesar A. Valdivia-Carrera; Ana C. Ho-Palma; Luis A. Gomez-Puerta; Daniel A. Andrade; Brenda L. Gonzales; Maria T. Lopez-Urbina; Armando E. Gonzalez; Javier A. Bustos; Hector H. Garcia; Sarah Gabriël; Seth E. O'Neal; Eloy Gonzales-Gustavson (Science of The Total Environment, 2025)

Variation in Biomass Yield and Cell Wall Composition in Switchgrass Natural Variants Under Two Nitrogen Regimes - Mitra Mazarei; Anne E. Harman-Ware; Thomas H. Pendergast; Vivek Shrestha; Yaping Xu; Cristiano Piasecki; Reginald J. Millwood; Katrien M. Devos; C. Neal Stewart (BioEnergy Research, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Next-generation marker-free transplastomic plants: engineering the chloroplast genome without integration of marker genes in Solanum tuberosum (potato) - Alessandro Occhialini; Andrew C. Reed; Stacee A. Harbison; Megan J. Sichterman; Aaron Baumann; Alexander C. Pfotenhauer; Li Li; Gabriella King; Aaron G. Vincent; Ashley D. Wise-Mitchell; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2024)

Comparison of direct and indirect soil organic carbon prediction at farm field scale - C. Segura; A.L. Neal; L. Castro-Sardiňa; P. Harris; M.J. Rivero; L.M. Cardenas; J.G.N. Irisarri (Journal of Environmental Management, 2024)

Robust soybean leaf agroinfiltration - Bryce N. Trull; Mst Shamira Sultana; Alexander C. Pfotenhauer; Jessica N. Stockdale; Vincent Pantalone; Bo Zhang; C. Neal Stewart (Plant Cell Reports, 2024)

Semantic processing in older adults is associated with distributed neural activation which varies by association and abstractness of words - Amanda Garcia; Ronald A. Cohen; Kailey G. Langer; Alexandria G. O’Neal; Eric C. Porges; Adam J. Woods; John B. Williamson (GeroScience, 2024)

Emerging from lockdown: Medical and sanitary waste on a Colombian beach during the first holiday season after COVID pandemic - Adriana Gracia C.; William J. Neal; Nelson Rangel-Buitrago (Marine Pollution Bulletin, 2024)

On-animal sensors may predict paddock level pasture mass in rotationally grazed dairy systems - J.P. Edwards; M. Qasim; R.H. Bryant; C. Thomas; C. Wright-Watson; G. Zobel; M.B. Neal; C.R. Eastwood (Computers and Electronics in Agriculture, 2024)

Drought stress-inducible synthetic promoters designed for poplar are functional in rice - Yongil Yang; Paolo Tagaloguin; Timothy A. Chaffin; Yuanhua Shao; Mitra Mazarei; Reginald J. Millwood; C. Neal Stewart (Plant Cell Reports, 2024)

AI to enable plant cell metabolic engineering - Robert G. Sears; Scott C. Lenaghan; C. Neal Stewart (Trends in Plant Science, 2024)

A spatially explicit model of landscape pesticide exposure to bees: Development, exploration, and evaluation - Eric V. Lonsdorf; Maj Rundlöf; Charlie C. Nicholson; Neal M. Williams (Science of The Total Environment, 2024)

Development of new binary expression systems for plant synthetic biology - Alexander C. Pfotenhauer; D. Nikki Reuter; Mikayla Clark; Stacee A. Harbison; Tayler M. Schimel; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2024)

The Impact of Homestyles-2 Nutrition Education Curriculum on Family Mealtime Behaviors, Supports, and Perceptions of Parents/Caregivers of Children Ages 6 to 11 - J. Zeldman; I. Ramirez; K. Chambers; L. Brunson; Y. Li; L. O'Neal; M. Olfert; C. Byrd-Bredbenner; K. Shelnutt (Journal of the Academy of Nutrition and Dietetics, 2023)

Rapid fuel recovery after stand-replacing fire in closed-cone pine forests and implications for short-interval severe reburns - Michelle C. Agne; Joseph B. Fontaine; Neal J. Enright; Sarah M. Bisbing; Brian J. Harvey (Forest Ecology and Management, 2023)

Dune ecosystems along the central Caribbean coast of Colombia: Evolution, human influences, and conservation challenges - Nelson Rangel-Buitrago; Adriana Gracia C; William J. Neal (Ocean & Coastal Management, 2023)

Corrigendum to “Swelling of compacted bentonite in organic solvents: Correlation of rate and extent of swelling with solvent properties” [Applied Clay Science 241 (2023) 107000] - Ali Riza Erdogan; Anna C. Whitford; Thomas R. Underwood; Catriona Sellick; Radhika Patel; Neal T. Skipper; H. Christopher Greenwell (Applied Clay Science, 2023)

Swelling of compacted bentonite in organic solvents: Correlation of rate and extent of swelling with solvent properties - Ali Reza Erdogan; Anna C. Whitford; Thomas R. Underwood; Catriona Sellick; Radhika Patel; Neal T. Skipper; H. Christopher Greenwell (Applied Clay Science, 2023)

In loving memory of Prof. A.T. Williams: A life dedicated to Coastal Geomorphology, Conservation and Management - Adriana Gracia C.; Andrew Cooper; Andrew Short; Anton Micallef; Ayşen Ergin; Carlos Pereira da Silva; Chris House; Enzo Pranzini; Frank van der Meulen; Julian Orford; Michael Phillips; Omar Alharbi; et al. (Ocean & Coastal Management, 2023)

Sperm processing methods effectively reduce the DNA fragmentation index in samples with high initial values - Bruno Joaquin Paredes; Camilo Hernández-Avilés; Luisa F Ramírez-Agámez; Laura A Favetta; Eduardo S Ribeiro; Mariana Diel Amorim; Michael S Neal; Charles C Love; Tracey Chenier (Journal of Equine Veterinary Science, 2023)

Authorship and the importance of the author contribution statement - C. Neal Stewart Jr; Gűnther Hahne (Plant Cell Reports, 2023)

Soil carbon, nitrogen, and biotic properties after long-term no-till and nitrogen fertilization in a subtropical Vertisol - Yaqi Zhang; Ranjan Bhattacharyya; Damien Finn; Henry W.G. Birt; Paul G. Dennis; Ram C. Dalal; Andrew R. Jones; Gregor Meyer; Buddhi Dayananda; Peng Wang; Neal W. Menzies; Peter M. Kopittke (Soil and Tillage Research, 2023)

Evaluating nutrient abatement policies for a pastorally farmed catchment-lagoon ecosystem: A New Zealand case study - Pierre C. Beukes; Marc Weeber; Mark Neal; Christophe Thiange; David F. Burger (Agriculture, Ecosystems & Environment, 2023)

A new section: plant systems biology/genome-wide studies - Günther Hahne; C. Neal Stewart (Plant Cell Reports, 2023)

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Recovery of a headwater stream population of brown trout after a fish kill in southeastern Minnesota, USA - Avery C. Schnaser; Neal D. Mundahl (Environmental Biology of Fishes, 2022)

Demographic processes underpinning post-fire resilience in California closed-cone pine forests: the importance of fire interval, stand structure, and climate - Michelle C. Agne; Joseph B. Fontaine; Neal J. Enright; Sarah M. Bisbing; Brian J. Harvey (Plant Ecology, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Proteinase inhibitors in legume herbivore defense: from natural to genetically engineered protectants - Mst Shamira Sultana; Reginald J. Millwood; Mitra Mazarei; C. Neal Stewart (Plant Cell Reports, 2022)

Stable isotope techniques for quantifying N fertiliser recovery in maize grown in soils with different management histories - Sarita Manandhar; Michael J. Bell; Ram C. Dalal; Neal W. Menzies; Cristina Martinez (Nutrient Cycling in Agroecosystems, 2022)

Plant Cell Reports turns 40 - Günther Hahne; C. Neal Stewart (Plant Cell Reports, 2021)

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Men’s experiences of radiotherapy treatment for localized prostate cancer and its long-term treatment side effects: a longitudinal qualitative study - E. Sutton; J. A. Lane; M. Davis; E. I. Walsh; D. E. Neal; F. C. Hamdy; M. Mason; J. Staffurth; R. M. Martin; C. Metcalfe; T. J. Peters; J. L. Donovan; et al. (Cancer Causes & Control, 2021)
Purpose To investigate men’s experiences of receiving external-beam radiotherapy (EBRT) with neoadjuvant Androgen Deprivation Therapy (ADT) for localized prostate cancer (LPCa) in the ProtecT trial. Methods A longitudinal qualitative interview study was embedded in the ProtecT RCT. Sixteen men with clinically LPCa who underwent EBRT in ProtecT were purposively sampled to include a range of socio-demographic and clinical characteristics. They participated in serial in-depth qualitative interviews for up to 8 years post-treatment, exploring experiences of treatment and its side effects over time. Results Men experienced bowel, sexual, and urinary side effects, mostly in the short term but some persisted and were bothersome. Most men downplayed the impacts, voicing expectations of age-related decline, and normalizing these changes. There was some reticence to seek help, with men prioritizing their relationships and overall health and well-being over returning to pretreatment levels of function. Some unmet needs with regard to information about treatment schedules and side effects were reported, particularly among men with continuing functional symptoms. Conclusions These findings reinforce the importance of providing universal clear, concise, and timely information and supportive resources in the short term, and more targeted and detailed information and care in the longer term to maintain and improve treatment experiences for men undergoing EBRT.

Long-Term Changes in Terrestrial Vegetation Linked to Shifts in a Colonial Seabird Population - Matthew P. Duda; John R. Glew; Neal Michelutti; Gregory J. Robertson; William A. Montevecchi; Jennifer A. Kissinger; David C. Eickmeyer; Jules M. Blais; John P. Smol (Ecosystems, 2020)

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Publication impacts: more than a number - C. Neal Stewart; Günther Hahne (Plant Cell Reports, 2020)

Systematic review and meta-analysis of the associations between body mass index, prostate cancer, advanced prostate cancer, and prostate-specific antigen - Sean Harrison; Kate Tilling; Emma L. Turner; Richard M. Martin; Rosie Lennon; J. Athene Lane; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. L. H. Ruud Bosch; Hayley E. Jones (Cancer Causes & Control, 2020)
Purpose The relationship between body mass index (BMI) and prostate cancer remains unclear. However, there is an inverse association between BMI and prostate-specific antigen (PSA), used for prostate cancer screening. We conducted this review to estimate the associations between BMI and (1) prostate cancer, (2) advanced prostate cancer, and (3) PSA. Methods We searched PubMed and Embase for studies until 02 October 2017 and obtained individual participant data from four studies. In total, 78 studies were identified for the association between BMI and prostate cancer, 21 for BMI and advanced prostate cancer, and 35 for BMI and PSA. We performed random-effects meta-analysis of linear associations of log-PSA and prostate cancer with BMI and, to examine potential non-linearity, of associations between categories of BMI and each outcome. Results In the meta-analyses with continuous BMI, a 5 kg/m 2 increase in BMI was associated with a percentage change in PSA of − 5.88% (95% CI − 6.87 to − 4.87). Using BMI categories, compared to normal weight men the PSA levels of overweight men were 3.43% lower (95% CI − 5.57 to − 1.23), and obese men were 12.9% lower (95% CI − 15.2 to − 10.7). Prostate cancer and advanced prostate cancer analyses showed little or no evidence associations. Conclusion There is little or no evidence of an association between BMI and risk of prostate cancer or advanced prostate cancer, and strong evidence of an inverse and non-linear association between BMI and PSA. The association between BMI and prostate cancer is likely biased if missed diagnoses are not considered.

Effect of e-cigarette flavors on nicotine delivery and puffing topography: results from a randomized clinical trial of daily smokers - Natalie Voos; Danielle Smith; Lisa Kaiser; Martin C. Mahoney; Clara M. Bradizza; Lynn T. Kozlowski; Neal L. Benowitz; Richard J. O’Connor; Maciej L. Goniewicz (Psychopharmacology, 2020)

Development and field assessment of transgenic hybrid switchgrass for improved biofuel traits - Lisa Alexander; Catherine Hatcher; Mitra Mazarei; Ellen Haynes; Holly Baxter; Keonhee Kim; Choo Hamilton; Robert Sykes; Geoffrey Turner; Mark Davis; Zeng-Yu Wang; Nicole Labbé; et al. (Euphytica, 2020)

Mismatched outcomes for biodiversity and ecosystem services: testing the responses of crop pollinators and wild bee biodiversity to habitat enhancement - Charlie C. Nicholson; Kimiora L. Ward; Neal M. Williams; Rufus Isaacs; Keith S. Mason; Julianna K. Wilson; Julia Brokaw; Larry J. Gut; Nikki L. Rothwell; Thomas J. Wood; Sujaya Rao; George D. Hoffman; et al. (Ecology Letters, 2020)
Supporting ecosystem services and conserving biodiversity may be compatible goals, but there is concern that service‐focused interventions mostly benefit a few common species. We use a spatially replicated, multiyear experiment in four agricultural settings to test if enhancing habitat adjacent to crops increases wild bee diversity and abundance on and off crops. We found that enhanced field edges harbored more taxonomically and functionally abundant, diverse, and compositionally different bee communities compared to control edges. Enhancements did not increase the abundance or diversity of bees visiting crops, indicating that the supply of pollination services was unchanged following enhancement. We find that actions to promote crop pollination improve multiple dimensions of biodiversity, underscoring their conservation value, but these benefits may not be spilling over to crops. More work is needed to identify the conditions that promote effective co‐management of biodiversity and ecosystem services.

Shifting perceptions of rapid temperature changes’ effects on marine fisheries, 1945–2017 - Loren McClenachan; Jonathan H. Grabowski; Madison Marra; C. Seabird McKeon; Benjamin P. Neal; Nicholas R. Record; Steven B. Scyphers (Fish and Fisheries, 2019)
Climate‐driven warming has both social and ecological effects on marine fisheries. While recent changes due to anthropogenic global warming have been documented, similar basin‐wide changes have occurred in the past due to natural temperature fluctuations. Here, we document the effects of rapidly changing water temperatures along the United States’ east coast using observations from fisheries newspapers during a warming phase (1945–1951) and subsequent cooling phase (1952–1960) of the Atlantic Multidecadal Oscillation, which we compared to similar recent observations of warming waters (1998–2017). Historical warming and cooling events affected the abundance of species targeted by fishing, the prevalence of novel and invasive species, and physical access to targeted species. Fishing communities viewed historical cooling waters twice as negatively as they did warming waters (72% vs. 35% of observations). Colder waters were associated with a decrease in fishing opportunity due to storminess, while warming waters were associated with the potential for new fisheries. In contrast, recent warming waters were viewed as strongly negative by fishing communities (72% of observations), associated with disease, reductions in abundances of target species, and shifts in distributions across jurisdictional lines. This increasing perception that warming negatively affects local fisheries may be due to an overall reduction of opportunity in fisheries over the past half century, an awareness of the relative severity of warming today, larger changes in American culture, or a combination of these factors. Negative perceptions of recent warming waters’ effects on fisheries suggest that fishing communities are currently finding the prospect of climate adaptation difficult.

Comparing 2D capabilities of HEC-RAS and LISFLOOD-FP on complex topography - Iuliia Shustikova; Alessio Domeneghetti; Jeffrey C. Neal; Paul Bates; Attilio Castellarin (Hydrological Sciences Journal, 2019)

Development and validation of a novel and robust cell culture system in soybean (Glycine max (L.) Merr.) for promoter screening - Mst. Shamira Sultana; Taylor P. Frazier; Reginald J. Millwood; Scott C. Lenaghan; C. Neal Stewart (Plant Cell Reports, 2019)

A global review and meta-analysis of applications of the freshwater Fish Invasiveness Screening Kit - Lorenzo Vilizzi; Gordon H. Copp; Boris Adamovich; David Almeida; Joleen Chan; Phil I. Davison; Samuel Dembski; F. Güler Ekmekçi; Árpád Ferincz; Sandra C. Forneck; Jeffrey E. Hill; Jeong-Eun Kim; et al. (Reviews in Fish Biology and Fisheries, 2019)

Discordant isolates in bone specimens from patients with recurrent foot osteomyelitis - Neal R. Barshes; Cezarina Mindru; Barbara W. Trautner; Maria C. Rodriguez-Barradas (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Commentary: Reconstructing Four Centuries of Temperature-Induced Coral Bleaching on the Great Barrier Reef - Ove Hoegh-Guldberg; William J. Skirving; Janice M. Lough; Chunying Liu; Michael E. Mann; Simon Donner; C. Mark Eakin; Neal Cantin; Jessica Carilli; Scott Fraser Heron; Sonya Miller; Sophie Dove (Frontiers in Marine Science, 2019)

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Absorption of foliar applied Zn is decreased in Zn deficient sunflower (Helianthus annuus) due to changes in leaf properties - Cui Li; Peng Wang; Enzo Lombi; Jingtao Wu; F. Pax C. Blamey; Victoria Fernández; Daryl L. Howard; Neal W. Menzies; Peter M. Kopittke (Plant and Soil, 2018)

Plant metabolic engineering in the synthetic biology era: plant chassis selection - C. Neal Stewart; Nicola Patron; Andrew D. Hanson; Joseph M. Jez (Plant Cell Reports, 2018)

The plastid genome as a chassis for synthetic biology-enabled metabolic engineering: players in gene expression - Heidi S. Schindel; Agnieszka A. Piatek; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2018)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

A profilin gene promoter from switchgrass (Panicum virgatum L.) directs strong and specific transgene expression to vascular bundles in rice - Wenzhi Xu; Wusheng Liu; Rongjian Ye; Mitra Mazarei; Debao Huang; Xinquan Zhang; C. Neal Stewart (Plant Cell Reports, 2018)

Climbing plants: attachment adaptations and bioinspired innovations - Jason N. Burris; Scott C. Lenaghan; C. Neal Stewart (Plant Cell Reports, 2018)

Nitrogen‐rich microbial products provide new organo‐mineral associations for the stabilization of soil organic matter - Peter M. Kopittke; Maria C. Hernandez‐Soriano; Ram C. Dalal; Damien Finn; Neal W. Menzies; Carmen Hoeschen; Carsten W. Mueller (Global Change Biology, 2018)
Understanding the cycling of C and N in soils is important for maintaining soil fertility while also decreasing greenhouse gas emissions, but much remains unknown about how organic matter ( OM ) is stabilized in soils. We used nano‐scale secondary ion mass spectrometry (Nano SIMS ) to investigate the changes in C and N in a Vertisol and an Alfisol incubated for 365 days with 13 C and 15 N pulse labeled lucerne ( Medicago sativa L.) to discriminate new inputs of OM from the existing soil OM . We found that almost all OM within the free stable microaggregates of the soil was associated with mineral particles, emphasizing the importance of organo‐mineral interactions for the stabilization of C. Of particular importance, it was also found that 15 N‐rich microbial products originating from decomposition often sorbed directly to mineral surfaces not previously associated with OM . Thus, we have shown that N‐rich microbial products preferentially attach to distinct areas of mineral surfaces compared to C‐dominated moieties, demonstrating the ability of soils to store additional OM in newly formed organo‐mineral associations on previously OM ‐free mineral surfaces. Furthermore, differences in 15 N enrichment were observed between the Vertisol and Alfisol presumably due to differences in mineralogy (smectite‐dominated compared to kaolinite‐dominated), demonstrating the importance of mineralogy in regulating the sorption of microbial products. Overall, our findings have important implications for the fundamental understanding of OM cycling in soils, including the immobilization and storage of N‐rich compounds derived from microbial decomposition and subsequent N mineralization to sustain plant growth.

Developing new age-specific prostate-specific antigen thresholds for testing for prostate cancer - Rebecca Gilbert; Kate Tilling; Richard M. Martin; J. Athene Lane; Michael Davis; Freddie C. Hamdy; David E. Neal; Jenny L. Donovan; Chris Metcalfe (Cancer Causes & Control, 2018)

Phytopathogen-induced changes to plant methylomes - Tarek Hewezi; Vince Pantalone; Morgan Bennett; C. Neal Stewart; Tessa M. Burch-Smith (Plant Cell Reports, 2018)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

The effect of salinity on plant-available water - Anna R. Sheldon; Ram C. Dalal; Gunnar Kirchhof; Peter M. Kopittke; Neal W. Menzies (Plant and Soil, 2017)

Atmospheric pollen dispersion from herbicide-resistant horseweed (Conyza canadensis L.) - Junming Wang; Meilan Qi; Haiyan Huang; Rongjian Ye; Xiangzhen Li; C. Neal Stewart (Aerobiologia, 2017)

Post-diagnosis serum insulin-like growth factors in relation to dietary and lifestyle changes in the Prostate testing for cancer and Treatment (ProtecT) trial - Vanessa Er; Kalina Biernacka; Andrew J. Simpkin; Richard M. Martin; Mona Jeffreys; Pauline Emmett; Rebecca Gilbert; Kerry N. L. Avery; Eleanor Walsh; Michael Davis; Jenny L. Donovan; David E. Neal; et al. (Cancer Causes & Control, 2017)
Purpose The insulin-like growth factor (IGF) system is modifiable by diet and lifestyle, and has been linked to prostate cancer development and progression. Methods We conducted a prospective cohort study of 621 men diagnosed with localized prostate cancer to investigate the associations of dietary and lifestyle changes with post-diagnosis circulating levels of IGF-I and IGFBP-3. We used analysis of covariance to estimate the associations, controlling for baseline IGF-I or IGFBP-3, respectively. Results Mean IGF-I levels were 6.5% (95% CI −12.8, −0.3%, p = 0.04) lower in men who decreased their protein intake after diagnosis compared to men who did not change. Men who changed their fruit and vegetable intake had lower IGF-I levels compared to non-changers [Decreased intake: −10.1%, 95% CI −18.4, −1.8%, p = 0.02; Increased intake: −12.0%, 95% CI −18.4, −1.8%, p = 0.002]. IGFBP-3 was 14.6% (95% CI −24.5, −4.8%, p = 0.004) lower in men who achieved a healthy body mass index after diagnosis. Men who became inactive had 9.5% higher average IGF-I levels (95% CI 0.1, 18.9%, p = 0.05). Conclusions Decreased protein intake and body mass index, and increased physical activity and fruit and vegetable intake, following a prostate cancer diagnosis were associated with reduced post-diagnosis serum IGF-I and IGFBP-3. Counterintuitively, reduced fruit and vegetable intake was also associated with reduced IGF-I, but with weak statistical support, possibly implicating chance. If confirmed in other studies, our findings may inform potential lifestyle interventions in prostate cancer. ProtecT was registered at International Standard Randomised Controlled Trial Registry, http://isrctn.org as ISRCTN20141297.

Global changes in soil stocks of carbon, nitrogen, phosphorus, and sulphur as influenced by long‐term agricultural production - Peter M. Kopittke; Ram C. Dalal; Damien Finn; Neal W. Menzies (Global Change Biology, 2017)
Quantifying changes in stocks of C, N, P, and S in agricultural soils is important not only for managing these soils sustainably as required to feed a growing human population, but for C and N, they are also important for understanding fluxes of greenhouse gases from the soil environment. In a global meta‐analysis, 102 studies were examined to investigate changes in soil stocks of organic C, total N, total P, and total S associated with long‐term land‐use changes. Conversion of native vegetation to cropping resulted in substantial losses of C (−1.6 kg m −2 , −43%), N (−0.15 kg m −2 , −42%), P (−0.029 kg m −2 , −27%), and S (−0.015 kg m −2 , −33%). The subsequent conversion of conventional cropping systems to no‐till, organic agriculture, or organic amendment systems subsequently increased stocks, but the magnitude of this increase (average of +0.47 kg m −2 for C and +0.051 kg m −2 for N) was small relative to the initial decrease. We also examined the conversion of native vegetation to pasture, with changes in C (−11%), N (+4.1%), and P (+25%) generally being modest relative to changes caused by conversion to cropping. The C:N ratio remained relatively constant irrespective of changes in land use, whilst in contrast, the C:S ratio decreased by 21% in soils converted to cropping – this suggesting that biochemical mineralization is of importance for S. The data presented here will assist in the assessment of different agricultural production systems on soil stocks of C, N, P, and S – this information assisting not only in quantifying the effects of existing agricultural production on these stocks, but also allowing for informed decision‐making regarding the potential effects of future land‐use changes.

Attenuating the alcohol allure: attentional broadening reduces rapid motivational response to alcohol pictures - Nicole C. Ryerson; Lauren B. Neal; Philip A. Gable (Psychopharmacology, 2017)

Growth and physiological responses of teak (Tectona grandis Linn. f.) clones to Ca, H and Al stresses in solution and acid soils - J. Bernhard Wehr; F. Pax C. Blamey; Tim E. Smith; Neal W. Menzies (New Forests, 2017)

Investigating the prostate specific antigen, body mass index and age relationship: is an age–BMI-adjusted PSA model clinically useful? - Sean Harrison; Kate Tilling; Emma L. Turner; J. Athene Lane; Andrew Simpkin; Michael Davis; Jenny Donovan; Freddie C. Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2016)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

A class of non-linear exposure-response models suitable for health impact assessment applicable to large cohort studies of ambient air pollution - Masoud M. Nasari; Mieczysław Szyszkowicz; Hong Chen; Daniel Crouse; Michelle C. Turner; Michael Jerrett; C. Arden Pope; Bryan Hubbell; Neal Fann; Aaron Cohen; Susan M. Gapstur; W. Ryan Diver; et al. (Air Quality, Atmosphere & Health, 2016)

Next-generation precision genome engineering and plant biotechnology - Magdy M. Mahfouz; Teodoro Cardi; C. Neal Stewart (Plant Cell Reports, 2016)

Progress of targeted genome modification approaches in higher plants - Teodoro Cardi; C. Neal Stewart (Plant Cell Reports, 2016)

Sulfur dynamics in sub-tropical soils of Australia as influenced by long-term cultivation - Peter M. Kopittke; Ram C. Dalal; Neal W. Menzies (Plant and Soil, 2016)

Hybridization of downregulated-COMT transgenic switchgrass lines with field-selected switchgrass for improved biomass traits - Holly L. Baxter; Lisa W. Alexander; Mitra Mazarei; Ellen Haynes; Geoffrey B. Turner; Robert W. Sykes; Stephen R. Decker; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (Euphytica, 2016)

A randomized, placebo-controlled pilot trial of the delta opioid receptor agonist AZD2327 in anxious depression - Erica M. Richards; Daniel C. Mathews; David A. Luckenbaugh; Dawn F. Ionescu; Rodrigo Machado-Vieira; Mark J. Niciu; Wallace C. Duncan; Neal M. Nolan; Jose A. Franco-Chaves; Thomas Hudzik; Carla Maciag; Shuang Li; et al. (Psychopharmacology, 2016)

Development of a rapid, low-cost protoplast transfection system for switchgrass (Panicum virgatum L.) - Kellie P. Burris; Elizabeth M. Dlugosz; A. Grace Collins; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2016)

Reduction of Ethanol Yield from Switchgrass Infected with Rust Caused by Puccinia emaculata - Virginia R. Sykes; Fred L. Allen; Jonathan R. Mielenz; C. Neal Stewart; Mark T. Windham; Choo Y. Hamilton; Miguel Rodriguez; Kelsey L. Yee (BioEnergy Research, 2016)

The presence of Bt-transgenic oilseed rape in wild mustard populations affects plant growth - Yongbo Liu; C. Neal Stewart; Junsheng Li; Hai Huang; Xitao Zhang (Transgenic Research, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Field Evaluation of Transgenic Switchgrass Plants Overexpressing PvMYB4 for Reduced Biomass Recalcitrance - Holly L. Baxter; Charleson R. Poovaiah; Kelsey L. Yee; Mitra Mazarei; Miguel Rodriguez; Olivia A. Thompson; Hui Shen; Geoffrey B. Turner; Stephen R. Decker; Robert W. Sykes; Fang Chen; Mark F. Davis; et al. (BioEnergy Research, 2015)

The effect of Bt-transgene introgression on plant growth and reproduction in wild Brassica juncea - Yong-Bo Liu; Henry Darmency; C. Neal Stewart; Wei Wei; Zhi-Xi Tang; Ke-Ping Ma (Transgenic Research, 2015)

Plant lipid biology and biotechnology - Mi Chung Suh; Günther Hahne; Jang R. Liu; C. Neal Stewart (Plant Cell Reports, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Farmer Involvement in the Development and Adoption of Improved Nutrient Management Technologies Using the Mother–Baby Trial Approach in Vertisols - K. Sammi Reddy; M. Mohanty; D. L. N. Rao; A. Subba Rao; M. Pandey; M. Singh; S. K. Dixit; Ram C. Dalal; F. Pax C. Blamey; Neal W. Menzies (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Spatially explicit estimation of aboveground boreal forest biomass in the Yukon River Basin, Alaska - Lei Ji; Bruce K. Wylie; Dana R. N. Brown; Birgit Peterson; Heather D. Alexander; Michelle C. Mack; Jennifer Rover; Mark P. Waldrop; Jack W. McFarland; Xuexia Chen; Neal J. Pastick (International Journal of Remote Sensing, 2015)

Ten-year retrospective assessment of the performance of the Food Contact Notification (FCN) programme - April Neal-Kluever; Jessica Cooper; Thomas C. Zebovitz; Kyla M. Butts (Food Additives & Contaminants: Part A, 2015)

Associations of vitamin D pathway genes with circulating 25-hydroxyvitamin-D, 1,25-dihydroxyvitamin-D, and prostate cancer: a nested case–control study - Rebecca Gilbert; Carolina Bonilla; Chris Metcalfe; Sarah Lewis; David M. Evans; William D. Fraser; John P. Kemp; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. Athene Lane; George Davey Smith; et al. (Cancer Causes & Control, 2015)

Genetic diversity analysis of switchgrass (Panicum virgatum L.) populations using microsatellites and chloroplast sequences - Madhugiri Nageswara-Rao; Micaha Hanson; Sujata Agarwal; C. Neal Stewart; Charles Kwit (Agroforestry Systems, 2014)

Physiological and transcriptional responses of Baccharis halimifolia to the explosive “composition B” (RDX/TNT) in amended soil - Asjad Ali; Julie C. Zinnert; Balasubramaniam Muthukumar; Yanhui Peng; Sang-Min Chung; C. Neal Stewart (Environmental Science and Pollution Research, 2014)

Kinetics and mechanisms of cowpea root adaptation to changes in solution calcium - F. Pax C. Blamey; J. Bernhard Wehr; Peng Wang; Neal W. Menzies; Peter M. Kopittke (Plant and Soil, 2014)

Images and imagination: the role of figures in plant cell and molecular biology publications - C. Neal Stewart (Plant Cell Reports, 2014)

Observing Global Surface Water Flood Dynamics - Paul D. Bates; Jefferey C. Neal; Douglas Alsdorf; Guy J.-P. Schumann (Surveys in Geophysics, 2014)

When depth is no refuge: cumulative thermal stress increases with depth in Bocas del Toro, Panama - B. P. Neal; C. Condit; G. Liu; S. dos Santos; M. Kahru; B. G. Mitchell; D. I. Kline (Coral Reefs, 2014)

Men with prostate cancer make positive dietary changes following diagnosis and treatment - Kerry N. L. Avery; Jenny L. Donovan; Rebecca Gilbert; Michael Davis; Pauline Emmett; Liz Down; Steven Oliver; David E. Neal; Freddie C. Hamdy; J. Athene Lane (Cancer Causes & Control, 2013)

Standardization of Switchgrass Sample Collection for Cell Wall and Biomass Trait Analysis - C. Frank Hardin; Chunxiang Fu; Hiroshi Hisano; Xirong Xiao; Hui Shen; C. Neal Stewart; Wayne Parrott; Richard A. Dixon; Zeng-Yu Wang (BioEnergy Research, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Ecological impacts of an invasive predator explained and predicted by comparative functional responses - Jaimie T. A. Dick; Kevin Gallagher; Suncica Avlijas; Hazel C. Clarke; Susan E. Lewis; Sally Leung; Dan Minchin; Joe Caffrey; Mhairi E. Alexander; Cathy Maguire; Chris Harrod; Neil Reid; et al. (Biological Invasions, 2013)

Genetic diversity and structure of natural and agronomic switchgrass (Panicum virgatum L.) populations - Madhugiri Nageswara-Rao; C. Neal Stewart; Charles Kwit (Genetic Resources and Crop Evolution, 2013)

Genes expressed by the biological control bacterium P seudomonas protegens Pf ‐5 on seed surfaces under the control of the global regulators GacA and RpoS - Teresa A. Kidarsa; Brenda T. Shaffer; Neal C. Goebel; Daniel P. Roberts; Jeffrey S. Buyer; Aaron Johnson; Donald Y. Kobayashi; T. Mark Zabriskie; Ian Paulsen; Joyce E. Loper (Environmental Microbiology, 2013)
Summary Gene expression profiles of the biological control strain P seudomonas protegens Pf ‐5 inhabiting pea seed surfaces were revealed using a whole‐genome oligonucleotide microarray. We identified genes expressed by Pf ‐5 under the control of two global regulators ( GacA and RpoS ) known to influence biological control and secondary metabolism. Transcript levels of 897 genes, including many with unknown functions as well as those for biofilm formation, cyclic diguanylate (c‐di‐ GMP ) signalling, iron homeostasis and secondary metabolism, were influenced by one or both regulators, providing evidence for expression of these genes by Pf ‐5 on seed surfaces. Comparison of the GacA and RpoS transcriptomes defined for Pf ‐5 grown on seed versus in broth culture overlapped, but most genes were regulated by GacA or RpoS under only one condition, likely due to differing levels of expression in the two conditions. We quantified secondary metabolites produced by Pf ‐5 and gacA and rpoS mutants on seed and in culture, and found that production profiles corresponded generally with biosynthetic gene expression profiles. Future studies evaluating biological control mechanisms can now focus on genes expressed by Pf ‐5 on seed surfaces, the habitat where the bacterium interacts with seed‐infecting pathogens to suppress seedling diseases.

Associations of adiponectin and leptin with stage and grade of PSA-detected prostate cancer: the ProtecT study - Anya Burton; Richard M. Martin; Jeff Holly; J. Athene Lane; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; Kate Tilling (Cancer Causes & Control, 2013)

The Cerro Olivo Complex: a pre-collisional Neoproterozoic magmatic arc in Eastern Uruguay - Henri Masquelin; Luis A. D'Avila Fernandes; Cristine Lenz; Carla C. Porcher; Neal J. McNaughton (International Geology Review, 2012)

A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom - Nicholas J. Young; Chris Metcalfe; David Gunnell; Mari-Anne Rowlands; J. Athene Lane; Rebecca Gilbert; Kerry N. L. Avery; Michael Davis; David E. Neal; Freddie C. Hamdy; Jenny Donovan; Richard M. Martin; et al. (Cancer Causes & Control, 2012)

Climate change projections and stratosphere–troposphere interaction - Adam A. Scaife; Thomas Spangehl; David R. Fereday; Ulrich Cubasch; Ulrike Langematz; Hideharu Akiyoshi; Slimane Bekki; Peter Braesicke; Neal Butchart; Martyn P. Chipperfield; Andrew Gettelman; Steven C. Hardiman; et al. (Climate Dynamics, 2012)

Gene expression profiling of resistant and susceptible soybean lines infected with soybean cyst nematode - Mitra Mazarei; Wusheng Liu; Hani Al-Ahmad; Prakash R. Arelli; Vincent R. Pantalone; C. Neal Stewart (Theoretical and Applied Genetics, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Agroinfiltration as a technique for rapid assays for evaluating candidate insect resistance transgenes in plants - Brian Michael Leckie; C. Neal Stewart (Plant Cell Reports, 2011)

Hyperspectral studies of transgenic oilseed rape - Hong Jiang; Wei Wei; Xiaodong Song; C. Neal Stewart; Guomo Zhou; Zishan Jiang; Qiuan Zhu; Shuquan Yu; Shaolin Peng (International Journal of Remote Sensing, 2011)

Crop residues and fertilizer nitrogen influence residue decomposition and nitrous oxide emission from a Vertisol - Wisal Muhammad; Sarah M. Vaughan; Ram C. Dalal; Neal W. Menzies (Biology and Fertility of Soils, 2011)

Sustainable Use of Biotechnology for Bioenergy Feedstocks - Hong S. Moon; Jason M. Abercrombie; Albert P. Kausch; C. Neal Stewart (Environmental Management, 2010)

Volcano collapse promoted by progressive strength reduction: new data from Mount St. Helens - Mark E. Reid; Terry E. C. Keith; Robert E. Kayen; Neal R. Iverson; Richard M. Iverson; Dianne L. Brien (Bulletin of Volcanology, 2010)

Comparative hydrolysis and sorption of Al and La onto plant cell wall material and pectic materials - J. Bernhard Wehr; F. Pax C. Blamey; Peter M. Kopittke; Neal W. Menzies (Plant and Soil, 2010)

A multi-center prospective cohort study of benign breast disease and risk of subsequent breast cancer - Geoffrey C. Kabat; Joan G. Jones; Neal Olson; Abdissa Negassa; Catherine Duggan; Mindy Ginsberg; Rita A. Kandel; Andrew G. Glass; Thomas E. Rohan (Cancer Causes & Control, 2010)

Toxicity of Cd to signal grass (Brachiaria decumbens Stapf.) and Rhodes grass (Chloris gayana Kunth.) - Peter M. Kopittke; F. Pax C. Blamey; Neal W. Menzies (Plant and Soil, 2010)

Inactivation of the GacA response regulator in Pseudomonas fluorescens Pf‐5 has far‐reaching transcriptomic consequences - Karl A. Hassan; Aaron Johnson; Brenda T. Shaffer; Qinghu Ren; Teresa A. Kidarsa; Liam D. H. Elbourne; Sierra Hartney; Robert Duboy; Neal C. Goebel; T. Mark Zabriskie; Ian T. Paulsen; Joyce E. Loper (Environmental Microbiology, 2010)
Summary The GacS/GacA signal transduction system is a central regulator in Pseudomonas spp., including the biological control strain P. fluorescens Pf‐5, in which GacS/GacA controls the production of secondary metabolites and exoenzymes that suppress plant pathogens. A whole genome oligonucleotide microarray was developed for Pf‐5 and used to assess the global transcriptomic consequences of a gacA mutation in P. fluorescens Pf‐5. In cultures at the transition from exponential to stationary growth phase, GacA significantly influenced transcript levels of 635 genes, representing more than 10% of the 6147 annotated genes in the Pf‐5 genome. Transcripts of genes involved in the production of hydrogen cyanide, the antibiotic pyoluteorin and the extracellular protease AprA were at a low level in the gacA mutant, whereas those functioning in siderophore production and other aspects of iron homeostasis were significantly higher in the gacA mutant than in wild‐type Pf‐5. Notable effects of gacA inactivation were also observed in the transcription of genes encoding components of a type VI secretion system and cytochrome c oxidase subunits. Two novel gene clusters expressed under the control of gacA were identified from transcriptome analysis, and we propose global‐regulator‐based genome mining as an approach to decipher the secondary metabolome of Pseudomonas spp.

China–U.S. workshop on biotechnology of bioenergy plants - C. Neal Stewart; Lee Shugart; Gong-She Liu; Jie Zhuang; Yongqing Ma; Gerald A. Tuskan; Richard Meilan; Randall W. Gentry; Gary S. Sayler (Ecotoxicology, 2010)

Rapid Assessment of Lignin Content and Structure in Switchgrass (Panicum virgatum L.) Grown Under Different Environmental Conditions - David G. J. Mann; Nicole Labbé; Robert W. Sykes; Kristen Gracom; Lindsey Kline; Isabella M. Swamidoss; Jason N. Burris; Mark Davis; C. Neal Stewart (BioEnergy Research, 2009)

An Improved Tissue Culture System for Embryogenic Callus Production and Plant Regeneration in Switchgrass (Panicum virgatum L.) - Jason N. Burris; David G. J. Mann; Blake L. Joyce; C. Neal Stewart (BioEnergy Research, 2009)

Phytoremediation and phytosensing of chemical contaminants, RDX and TNT: identification of the required target genes - Murali R. Rao; Matthew D. Halfhill; Laura G. Abercrombie; Priya Ranjan; Jason M. Abercrombie; Julia S. Gouffon; Arnold M. Saxton; C. Neal Stewart (Functional & Integrative Genomics, 2009)

Nitrous oxide emission from feedlot manure and green waste compost applied to Vertisols - Ram C. Dalal; Iain R. Gibson; Neal W. Menzies (Biology and Fertility of Soils, 2009)

Distribution of nitrogen-15 tracers applied to the canopy of a mature spruce-hemlock stand, Howland, Maine, USA - David Bryan Dail; David Y. Hollinger; Eric A. Davidson; Ivan Fernandez; Herman C. Sievering; Neal A. Scott; Elizabeth Gaige (Oecologia, 2009)

Differential expression of genes in soybean in response to the causal agent of Asian soybean rust (Phakopsora pachyrhizi Sydow) is soybean growth stage-specific - Dilip R. Panthee; James J. Marois; David L. Wright; Dario Narváez; Joshua S. Yuan; C. Neal Stewart (Theoretical and Applied Genetics, 2009)

Physical activity and head and neck cancer risk - Michael F. Leitzmann; Corinna Koebnick; Neal D. Freedman; Yikyung Park; Rachel Ballard-Barbash; Albert R. Hollenbeck; Arthur Schatzkin; Christian C. Abnet (Cancer Causes & Control, 2008)

Fruit and vegetable intake and gastric cancer risk in a large United States prospective cohort study - Neal D. Freedman; Amy F. Subar; Albert R. Hollenbeck; Michael F. Leitzmann; Arthur Schatzkin; Christian C. Abnet (Cancer Causes & Control, 2008)

Interactions of elevated carbon dioxide and temperature with aphid feeding on transgenic oilseed rape: Are Bacillus thuringiensis (Bt) plants more susceptible to nontarget herbivores in future climate? - SARI J. HIMANEN; ANNE NISSINEN; WEN‐XIA DONG; ANNE‐MARJA NERG; C. NEAL STEWART; GUY M. POPPY; JARMO K. HOLOPAINEN (Global Change Biology, 2008)
Climate change factors such as elevated carbon dioxide (CO 2 ) and temperature typically affect carbon (C) and nitrogen (N) dynamics of crop plants and the performance of insect herbivores. Insect‐resistant transgenic plants invest some nutrients to the production of specific toxic proteins [i.e. endotoxins from Bacillus thuringiensis (Bt)], which could alter the C–N balance of these plants, especially under changed abiotic conditions. Aphids are nonsusceptible to Lepidoptera‐targeted Bt Cry1Ac toxin and they typically show response to abiotic conditions, and here we sought to discover whether they might perform differently on compositionally changed Bt oilseed rape. Bt oilseed rape had increased N content in the leaves coupled with reduced total C compared with its nontransgenic counterpart, but in general the C : N responses of both plant types to elevated CO 2 and temperature were similar. Elevated CO 2 decreased N content and increased C : N ratio of both plant types. Elevated temperature increased C and N contents, total chlorophyll and carotenoid concentrations under ambient CO 2 , but decreased these under elevated CO 2 . In addition, soluble sugars were increased and starch decreased by elevated temperature under ambient but not under elevated CO 2 , whereas photosynthesis was decreased in plants grown under elevated temperature in both CO 2 levels. Myzus persicae , a generalist aphid species, responded directly to elevated temperature with reduced developmental time and decreased adult and progeny weights, whereas the development of the Brassica specialist Brevicoryne brassicae was less affected. Feeding by M. persicae resulted in an increase in the N content of oilseed rape leaves under ambient CO 2 , indicating the potential of herbivore feeding itself to cause allocation changes. The aphids performed equally well on both plant types despite the differences between C–N ratios of Bt and non‐Bt oilseed rape, revealing the absence of plant composition‐related effects on these pests under elevated CO 2 , elevated temperature or combined elevated CO 2 and temperature conditions.

Stable isotope profiles of partially migratory salmonid populations in Atlantic rivers of Patagonia - J. E. Ciancio; M. A. Pascual; F. Botto; M. Amaya‐Santi; S. O’Neal; C. Riva Rossi; O. Iribarne (Journal of Fish Biology, 2008)
In the present study, profiles of stable isotope composition were characterized for two species with partially migratory populations in rivers along the latitudinal gradient of Patagonia, brown trout Salmo trutta and rainbow trout Oncorhynchus mykiss . The effects of factors ( e.g. ontogeny of fishes, location, species and fasting) that may influence the stable isotope analysis (SIA) were evaluated, as was SIA evaluated as a tool to assign individual fish to their corresponding ecotype. Anadromous fishes exhibited enriched δ 15 N (15·2 ± 1·0‰; mean ± s . d .) and δ 13 C (−19·2 ± 1·3‰) relative to resident fishes’δ 15 N (8·8 ± 1·1‰) and δ 13 C (−23·2 ± 2·5‰). For both species, the difference in δ 15 N was larger between resident (range 6·8–10·7‰) and anadromous (range 14·3–17·8‰) fishes than that in δ 13 C. Values of δ 13 C, while not as dramatically contrasting in rainbow trout, provided a powerful anadromy marker for brown trout in the region. Increases were found in both δ 15 N and δ 13 C during the spawning migration of anadromous rainbow trout, most likely due to fasting. Differences in stable isotopes between location, size and species were found, suggesting different stable isotopes base levels in freshwater environments and different trophic levels and feeding location of anadromous populations. The SIA was demonstrated as a powerful tool for ecotype discrimination in Patagonian Rivers, overriding any effect of sampling location, size or species.

Constitutive and herbivore-inducible glucosinolate concentrations in oilseed rape (Brassica napus) leaves are not affected by Bt Cry1Ac insertion but change under elevated atmospheric CO2 and O3 - Sari J. Himanen; Anne Nissinen; Seppo Auriola; Guy M. Poppy; C. Neal Stewart; Jarmo K. Holopainen; Anne-Marja Nerg (Planta, 2008)

Characterization of directly transformed weedy Brassica rapa and introgressed B. rapa with Bt cry1Ac and gfp genes - Hong S. Moon; Matthew D. Halfhill; Laura L. Good; Paul L. Raymer; C. Neal Stewart (Plant Cell Reports, 2007)

Transformation and segregation of GFP fluorescence and glyphosate resistance in horseweed (Conyza canadensis) hybrids - Matthew D. Halfhill; Laura L. Good; Chhandak Basu; Jason Burris; Christopher L. Main; Thomas C. Mueller; C. Neal Stewart (Plant Cell Reports, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Coupling of a 3D Finite Element Model of Cardiac Ventricular Mechanics to Lumped Systems Models of the Systemic and Pulmonic Circulation - Roy C. P. Kerckhoffs; Maxwell L. Neal; Quan Gu; James B. Bassingthwaighte; Jeff H. Omens; Andrew D. McCulloch (Annals of Biomedical Engineering, 2006)

Prey-mediated effects of transgenic canola on a beneficial, non-target, carabid beetle - Natalie Ferry; Evan A. Mulligan; C. Neal Stewart; Bruce E. Tabashnik; Gordon R. Port; Angharad M. R. Gatehouse (Transgenic Research, 2006)

Characterization of the novel CYP2A6*21 allele using in vivo nicotine kinetics - Nael Al Koudsi; Jill C. Mwenifumbo; Edward M. Sellers; Neal L. Benowitz; Gary E. Swan; Rachel F. Tyndale (European Journal of Clinical Pharmacology, 2006)

The Purkinje cell degeneration 5J mutation is a single amino acid insertion that destabilizes Nna1 protein - Lisa Chakrabarti; James T. Neal; Michael Miles; Refugio A. Martinez; Annette C. Smith; Bryce L. Sopher; Albert R. La Spada (Mammalian Genome, 2006)

Laser-Induced Fluorescence Imaging and Spectroscopy of GFP Transgenic Plants - C. Neal Stewart; Reginald J. Millwood; Matthew D. Halfhill; Mentewab Ayalew; Vinitha Cardoza; Mitra Kooshki; Gene A. Capelle; Kevin R. Kyle; David Piaseki; Gregory McCrum; John Di Benedetto (Journal of Fluorescence, 2005)

Growth, productivity, and competitiveness of introgressed weedy Brassica rapa hybrids selected for the presence of Bt cry1Ac and gfp transgenes - MATTHEW D. HALFHILL; JAMIE P. SUTHERLAND; HONG SEOK MOON; GUY M. POPPY; SUZANNE I. WARWICK; ARTHUR K. WEISSINGER; THOMAS W. RUFTY; PAUL L. RAYMER; C. NEAL STEWART (Molecular Ecology, 2005)
Concerns exist that transgenic crop × weed hybrid populations will be more vigorous and competitive with crops compared with the parental weed species. Hydroponic, glasshouse, and field experiments were performed to evaluate the effects of introgression of Bacillus thuringiensis (Bt) cry1Ac and green fluorescent protein (GFP) transgenes on hybrid productivity and competitiveness in four experimental Brassica rapa × transgenic Brassica napus hybrid generations (F 1 , BC 1 F 1 , BC 2 F 1 and BC 2 F 2 ). The average vegetative growth and nitrogen (N) use efficiency of transgenic hybrid generations grown under high N hydroponic conditions were lower than that of the weed parent ( Brassica rapa , AA, 2n = 20), but similar to the transgenic crop parent, oilseed rape ( Brassica napus , AACC, 2n = 38). No generational differences were detected under low N conditions. In two noncompetitive glasshouse experiments, both transgenic and nontransgenic BC 2 F 2 hybrids had on average less vegetative growth and seed production than B. rapa . In two high intraspecific competition field experiments with varied herbivore pressure, BC 2 F 2 hybrids produced less vegetative dry weight than B. rapa . The competitive ability of transgenic and nontransgenic BC 2 F 2 hybrids against a neighbouring crop species were quantified in competition experiments that assayed wheat ( Triticum aestivum ) yield reductions under agronomic field conditions. The hybrids were the least competitive with wheat compared with parental Brassica competitors, although differences between transgenic and nontransgenic hybrids varied with location. Hybridization, with or without transgene introgression, resulted in less productive and competitive populations.

Prevalence of Chemical Defenses among Freshwater Plants - Anne C. Prusak; Jennifer O’Neal; Julia Kubanek (Journal of Chemical Ecology, 2005)

Effect of menthol on the pharmacokinetics and pharmacodynamics of felodipine in healthy subjects - Ayse Gelal; Dilara Balkan; Deniz Ozzeybek; Yusuf C. Kaplan; Selma Gurler; Hulya Guven; Neal L. Benowitz (European Journal of Clinical Pharmacology, 2005)

Brassica biotechnology: Progress in cellular and molecular biology - Vinitha Cardoza; C. Neal Stewart (In Vitro Cellular & Developmental Biology - Plant, 2004)

Dopamine agonists disrupt visual latent inhibition in normal males using a within-subject paradigm - Neal R. Swerdlow; Nora Stephany; Lindsay C. Wasserman; Jo Talledo; Richard Sharp; Pamela P. Auerbach (Psychopharmacology, 2003)

Mechanisms for changes in soil carbon storage with pasture to Pinus radiata land‐use change - Joanne C. Halliday; Kevin R. Tate; Ross E. McMurtrie; Neal A. Scott (Global Change Biology, 2003)
In this study, we simulated pasture to Pinus radiata land‐use change with the G eneric D ecomposition A nd Y ield (G'DAY) ecosystem model to examine mechanisms responsible for the change in soil carbon (C) under pine. We parameterized the model for paired sites in New Zealand. Our simulations successfully reproduced empirical trends in ecosystem productivity and soil inorganic nitrogen (N), and modeled an increase in soil C and a small decline in soil N after 30 years under pine. We determined the mechanisms contributing to soil C change based on an established hypothesis that attributes increases in soil C storage to three main factors: increased ecosystem N inputs relative to outputs, increased C/N ratios in plant and soil, or a shift of N from plant to soil. The mechanisms we attributed to the simulated increase in soil C under pine were increased soil C inputs through tree litterfall, and an increase in the soil C/N ratio. In the first 7 years following pine establishment, a decline in soil C was simulated; this was matched by a decline in soil N. The simulated longer‐term increase in soil C with afforestation by pine contrasts with results from published field studies, which show either a decline or no change in soil C under pine. The discrepancy between measured and simulated changes in soil C was attributed to the G'DAY model overestimating the transfer of litter C into the mineral soil.

Tritrophic Choice Experiments with Bt Plants, the Diamondback Moth (Plutella xylostella) and the parasitoid Cotesia plutellae - Tanja H. Schuler; Roel P.J. Potting; Ian Denholm; Suzanne J. Clark; Alison J. Clark; C. Neal Stewart; Guy M. Poppy (Transgenic Research, 2003)

Screening of soybean, Glycine max L.) Merrill, lines for somatic embryo induction and maturation capability from immature cotyledons - Elizabeth S. Tomlin; Sheila R. Branch; Dean Chamberlain; Howard Gabe; Martha S. Wright; C. Neal Stewart (In Vitro Cellular & Developmental Biology - Plant, 2002)

A Role for Oxidative Stress in Suppressing Serum Immunoglobulin Levels in Lead-Exposed Fisher 344 Rats - N. Ercal; R. Neal; P. Treeratphan; P. M. Lutz; T. C. Hammond; P. A. Dennery; D. R. Spitz (Archives of Environmental Contamination and Toxicology, 2000)

Patterns of green fluorescent protein expression in transgenic plants - Brian K. Harper; C. Neal Stewart (Plant Molecular Biology Reporter, 2000)

Human skeletal myosin heavy chain genes are tightly linked in the order embryonic-IIa-IId/x-IIb-perinatal-extraocular - Joseph B. Shrager; Philippe R. Desjardins; James M. Burkman; Stephane K. Konig; Douglas R. Stewart; Leonard Su; Megha C. Shah; Evelyn Bricklin; Manu Tewari; Rebecca Hoffman; Michael R. Rickels; Eric H. Jullian; et al. (Journal of Muscle Research and Cell Motility, 2000)

Hydrogeochemistry of a Small Catchment in Northeastern Amazonia: a Comparison Between Natural with Deforested Parts of the Catchment (Serra do Navio, Amapá State, Brazil) - M. C. Forti; R. Boulet; A. J. Melfi; C. Neal (Water, Air, & Soil Pollution, 2000)

The thrombospondin-4 gene - Gail Newton; Stanislawa Weremowicz; Cynthia C. Morton , , Nancy A.; Debra J. Gilbert; Neal G. Copeland; Jack Lawler (Mammalian Genome, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Tsunami generation by pyroclastic flow during the 3500-year B.P. caldera-forming eruption of Aniakchak Volcano, Alaska - C. F. Waythomas; C. A. Neal (Bulletin of Volcanology, 1998)

Genetic mapping of the galanin-GMAP (Galn) gene to mouse Chromosome 19 - Leticia C. Guida; Philippa Charlton; Debra J. Gilbert; Nancy A. Jenkins; Neal G. Copeland; Robert D. Nicholls (Mammalian Genome, 1998)

Modification of the Copolymers Poloxamer 407 and Poloxamine 908 can Affect the Physical and Biological Properties of Surface Modified Nanospheres - Jonathan C. Neal; S. Stolnik; M. C. Garnett; Stanley S. Davis; Lisbeth Illum (Pharmaceutical Research, 1998)

cDNA cloning and chromosomal mapping of mouse fast skeletal muscle troponin T - Anne Koch; Todd S. -C. Juan; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Ian K. McNiece; Frederick A. Fletcher (Mammalian Genome, 1997)

Autumn use of woody snags by fishes in backwater and channel border habitats of a large river - Richard M. Lehtinen; Neal D. Mundahl; Jeffrey C. Madejczyk (Environmental Biology of Fishes, 1997)

Effects of selected inhibitors on growth and cell division inAgmenellum - Lonnie O'Neal Ingram; E. L. Thurston; C. Baalen (Archives of Microbiology, 1972)